N Mineralisation from Bioresources Incubated at 12.5°C - S. W. Ives; L. A. Sparrow; W. E. Cotching; R. B. Doyle; S. Lisson (Applied and Environmental Soil Science)
Soils treated with lime-amended biosolids (LAB), poppy seed waste (PSW), anaerobically digested biosolids (ADB) and poppy mulch (PM) and incubated at 12.5°C for 56 days released 45%, 36%, 25%, and −8%, respectively, of total applied N as plant available nitrogen (PAN) by the end of the incubation. The mineralisation rates were contrary to expectations based on the C : N ratios of the four products: LAB (5 : 1), PSW (7 : 1), ADB (3 : 1), and PM (16 : 1). PM showed a significant negative priming effect over the incubation period. These results have implications for production agriculture in temperate regions where application and incorporation of bio-resources traditionally occurs in autumn and spring when soil and air temperatures are relatively low. Current application times may not be suitable for nitrogen release to satisfy crop demand.